Outbreaks of salmonellosis caused by Salmonella typhisuis in Rio de Janeiro swine - Langenegger, Charlotte Hubinger; Langenegger, Jerome (Pesquisa Agropecuaria Brasileira, 2014)
The infection is described in two herds from two different districts. Young pigs of 3 to 5 months of age were the most frequently infected. The disease developed to death in one to three weeks, showing continuous or intermittent diarrhoea, progressive anorrhexia, dullness,  ematiation and slow hypertermia. The mortality was approximately 40% of the same litter mates. The post mortem, in all the cases, was caracterized by necrotic caseous colitis and mesenteric lymphadenitis. No diagnostic lesions were found in any other viscera. Salmonella typhisuis was easely isolated from the lesions of the intestine and mesenteric lymphnodes and from apparently normal liver and spleen. Many strains were identified by bioquimical behaviour and serologic typing. The antigenic structure was VI, VII : c 1,5. It was not found any reference about Salmonella typhisuis in animals in Brazil.
Keywords: Caseous enteritis; necrotic infections enteritis; salmonellosis